RNA binding Motif protein-38 regulates myocardial hypertrophy in LXR-α-dependent lipogenesis pathway. Issue 2 (20th December 2021) - Li, Yao; Shi, Yanhu; He, Yaoli; Li, Xiaoming; Yang, Junlu
ABSTRACT: Myocardial hypertrophy is a pathological thickening of the myocardium, leading to various ailments, such as myocardial infarction and heart failure. RBM38 is critical in modulating mRNA translation for multiple protective activities such as p53 tumor repressor and p21 kinase cell cycle inhibitors. Liver X receptors (LXR-α) agonists reduce cellular hypertrophy initiated by various hypertrophic stimuli as lipopolysaccharides and Ang II. This research investigates the possible cooperation between RBM38 and LXR-α and mechanisms in modulating myocardial hypertrophy. H9C2 cells were treated with PE, TNF-α, and AngII to induce myocardial hypertrophy. RBM38 and LXR- α were overexpressed or silenced in H9C2 cells, and hypertrophy markers (ANF and Myh7) were determined with Western blot and RT-qPCR. Binding assays were done through RNA immunoprecipitation. H&E and Rhodamine-labeled phalloidin staining assays were used to assess the relative cell surface change. The results demonstrated RBM38 downregulation in in vitro models of myocardial hypertrophy. Modulation of RBM38 expression also exerted inverse effects on myocardial hypertrophy markers. Further observations also showed that LXR-α expression regulates the myocardial hypertrophy markers in H9C2 cells and RBM38 binds with LXR-α mRNA, consequently inhibiting LXR-α expression. Finally, overexpression of RBM38 rescues Angiotensin II–induced myocardial hypertrophy by regulating LXR-α dependent lipogenesis pathway. In conclusion, RBM38 Overexpression rescues Angiotensin II–induced myocardial hypertrophy by regulating LXR-α dependent lipogenesis pathway.